The marshmallow incident - Barrett, Judi.; Barrett, Ron (New York : Scholastic Press, 2009)
The left-handed residents of the town of Left and the right-handed residents of the town of Right become friends after a marshmallow-throwing incident instigated by the knights of the Ambidextrous Order who guard the dotted yellow line that separates the two towns.
4.3
K-3
Keywords: Left- and right-handedness -- Juvenile fiction; Marshmallow -- Juvenile fiction; Left- and right-handedness -- Fiction; Marshmallow -- Fiction; Humorous stories; Left- and right-handedness -- Fiction; Marshmallow -- Fiction; Humorous fiction; Humorous fiction; Picture books for children